Surgical endodontic retreatment of a tooth with extensive periapical lesion: case report (Research, Society and Development, 2022)
This paper aims to describe a clinical case of surgical endodontic retreatment of a maxillary lateral incisor (tooth 12) with overfilling and extensive periapical lesion. A male patient was referred for endodontic retreatment of tooth 12. The intraoral examination revealed the presence of a fistula near teeth 11 and 12; and a positive response was obtained for the vertical percussion and mobility tests on tooth 12. The radiographic examination showed overfilling and an extensive radiolucent area associated with the root apex of teeth 11 and 12. In view of the history and radiographic findings, a computed tomography scan was requested. of conical beam, which showed great bone resorption in the apical region of tooth 12 with loss of buccal cortical bone and overfilling with gutta percha transposition through the apex of teeth 11 and 12. After consultations for failed endodontic retreatment, it was decided to perform a surgical endodontic retreatment with apical curettage, apicectomy, retrograde obturation and intracanal intraoperative obturation in tooth 12 and apicectomy with apical curettage in tooth 11. A Bio-C Repair bioceramic repair cement was used in the apical seal. During radiographic follow-up of 10 months, we can observe the absence of painful symptoms, of fistula and regression of the periapical lesion. Faced with persistent symptoms after conventional endodontic therapies, the endodontist should consider surgical treatment as a solution. Given the limitations, the correct management of this case can be attributed to the chosen surgical technique associated with the repair material used, which has excellent physicochemical and biological properties, which together helped to obtain the best possible result.